Putting the Individual in Ambidexterity – Identifying Activities to Achieve Organisational Ambidexterity and Long-Term Survival - Benedikt Schnellbaecher; Ulf Diefenbach; Jan Millemann (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Vast research is dedicated to enable companies to exploit existing knowledge to optimize processes as well as to explore new ways to conduct business. In other words how to achieve organisational ambidexterity. Previous research focuses mainly on ambidexterity at organisational or business unit level. Only few papers provide answers for academics or practitioners, what specific individual activities have to be pursuit for ambidexterity. The aim of the paper is to mitigate this research gap by screening research on organisational ambidexterity and filter out findings concerning individual ambidexterity. Applying a systematic review approach, the paper reviews academic literature and identifies knowledge seeking and knowledge offer as the core activities of individual ambidexterity. Building on this, a review is conducted to identify the antecedents of knowledge seeking and offer. Finally, the antecedents are structured according to its relevance in the knowledge adoption process. Thus, the paper contributes to research by providing a state of the art, conceptual base for further investigations into the individual ambidexterity topic.
Keywords: O31; D83; 330; Organisational ambidexterity; Individual ambidexterity; Knowledge seeking; Knowledge offer